Dynamic contrast-enhanced MRI for treatment response assessment in patients with oesophageal cancer receiving neoadjuvant chemoradiotherapy. Issue 1 (July 2016) - Heethuis, Sophie E.; van Rossum, Peter S.N.; Lips, Irene M.; Goense, Lucas; Voncken, Francine E.; Reerink, Onne; van Hillegersberg, Richard; Ruurda, Jelle P.; Philippens, Marielle E.; van Vulpen, Marco; Meijer, Gert J.; Lagendijk, Jan J.W.; et al.
Abstract: Purpose: To explore and evaluate the potential value of dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI) for the prediction of pathologic response to neoadjuvant chemoradiotherapy (nCRT) in oesophageal cancer. Material and methods: Twenty-six patients underwent DCE-MRI before, during (week 2–3) and after nCRT, but before surgery (pre/per/post, respectively). Histopathologic tumour regression grade (TRG) was assessed after oesophagectomy. Tumour area-under-the-concentration time curve (AUC), time-to-peak (TTP) and slope were calculated. The ability of these DCE-parameters to distinguish good responders (GR, TRG 1–2) from poor responders (noGR, TRG ⩾ 3), and pathologic complete responders (pCR) from no-pCR was assessed. Results: Twelve patients (48%) showed GR of which 8 patients (32%) pCR. Analysis of AUC change throughout treatment, AUCper-pre, was most predictive for GR, at a threshold of 22.7% resulting in a sensitivity of 92%, specificity of 77%, PPV of 79%, and a NPV of 91%. AUCpost-pre was most predictive for pCR, at a threshold of −24.6% resulting in a sensitivity of 83%, specificity of 88%, PPV of 71%, and a NPV of 93%. TTP and slope were not associated with pathologic response. Conclusions: This study demonstrates that changes in AUC throughout treatment are promising for prediction of histopathologic response to nCRT for oesophageal cancer.